Sphingorhabdus pulchriflava sp. nov., isolated from a river. Issue 9 (4th June 2019) - Jung, Gi-Yong; Nam, In-Hyun; Han, Yong-Soo; Ahn, Joo Sung; Rhee, Sung-Keun; Kim, So-Jeong
Abstract : A facultatively anaerobic and Gram-stain-negative bacterium, strain GY_G T, was isolated from a river (Daedeock-cheon) in Daejeon, Republic of Korea. The isolate was catalase-positive, oxidase-positive and formed yellow colonies. Strain GY_G T was phylogenetically classified as belonging in the genus Sphingorhabdus . Its closely related strains were Sphingorhabdus wooponensis 03SU3-P T (97.1 % similarity), Sphingorhabdus buctiana T5 T (96.9 %), Sphingorhabdus contaminans JC216 T (96.5 %), Sphingorhabdus rigui 01SU5-P T (96.5 %) and Sphingorhabdus planktonica G1A_585 T (96.3 %) based on 16S rRNA gene sequences. The growth conditions for GY_G T were at 10–45 °C (optimum, 25 °C), pH 6–10 (pH 7) and 0–4% NaCl (0.5–1.5 %). Strain GY_G T could utilize turanose, d -fructose-6-phosphate, glucuronamide, α -keto-glutaric acid and acetoacetic acid. The major fatty acids of strain GY_G T were summed features 8 (C18 : 1 ω 7 c /C18 : 1 ω 6 c ; 40.6 %) and 3 (C16 : 1 ω 6 c /C16 : 1 ω 7 c ; 24.7 %). The major quinone required for respiration was Q-10. The polar lipids of strain GY_G T were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and sphingolipid. The G+C content of the genome was 57.7 mol%. The average nucleotide identity and average amino acid identity values between strains GY_G T and S. wooponensis were 71.0 and 72.7 %, respectively. Based on phylogenetic and phenotypic attributes, we suggest that strain GY_G T is a novel species in the genus Sphingorhabdus and propose the name Sphingorhabdus pulchriflava . The type strain is GY_G T (=KCTC 62791 T =JCM 32855 T ).